Budaya Literasi sebagai Strategi Psikopedagogis dalam Membangun Growth Mindset pada Peserta Didik - Ulil Abshar; Fatur Rahman; Mohammad Riefyal Moulana (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2025)
This article examines the role of literacy culture as a psychopedagogical strategy in fostering a growth mindset among students in Aceh. The study adopts a conceptual literature review with a descriptive-analytical approach. Findings indicate that literacy activities such as reflective reading and discussion enhance intrinsic motivation, perseverance, and a growth-oriented mindset. Community-based approaches, such as utilizing coffee shops as literacy spaces, effectively expand the learning ecosystem. This study contributes to the development of contextual and adaptive character education strategies grounded in literacy.